Nutritional quality of edible winged termites, Macrotermes spp. and edible stink bug, Encosternum delegorguei Spinola consumed in sub-Saharan Africa: a scoping review - Tendai Abgirl Makore; Brighton Marimanzi Mvumi; Tonderayi Mathew Matsungo (Discover Food)
Abstract Background Entomophagy presents a viable solution to food and nutrition insecurity in sub-Saharan Africa (SSA), especially in the context of climate change, population growth, and limited land for agricultural expansion. Although insect consumption is widespread in SSA, there is limited commercialization or promotion to enhance uptake. Objective The review explored studies that reported the nutritional profiles of edible winged termites and stinkbugs consumed in SSA. Methods The study screened 23 studies from a total of 388 published between 2000 and 2024, using various databases, including Science Direct, PubMed, Web of Science, Google Scholar, Researchgate, Scopus and Google, following the PRISMA-ScR guidelines. Findings The review included 23 studies published between 2000 and 2024, focusing on winged termites Macrotermes spp (15 studies) and edible stinkbugs, Encosternum delegorguei (8 studies). The review revealed considerable variability in the nutritional composition of these insects across different SSA countries. Both insects are rich in protein (27.9–43.3%), fats (38.9–66.7%), crude fibre (0.2–16.4%), and moisture content (3.1–15.1%), along with essential minerals like iron and zinc with a maximum content of (70.7–111.8 mg/100 g) and zinc (4.4–16.2 mg/100 respectively. Some insects have higher protein content than chicken (43%), and their low moisture levels make them suitable for long-term storage and reduce microbial spoilage risks. Conclusions Geographical origin and species-specific traits influence nutritional profiles, while protein levels vary due to a lack of standard conversion factor. For successful market integration, further studies are needed to understand effects of processing methods and soil characteristics, and consumer acceptance of insect-based food.